Magnetic properties of the 6H Perovskite Ba3Fe2TeO9 - Tang, Y; Sena, RP; Avdeev, M; Battle, PD; Hunter, EC (Elsevier, 2017)
A polycrystalline sample of Ba3Fe2TeO9 having the 6H perovskite structure has been prepared in a solid-state reaction and studied by a combination of electron microscopy, Mössbauer spectroscopy, magnetometry, X-ray diffraction and neutron diffraction. Partial ordering of Fe3+ and Te6+ cations occurs over the six-coordinate sites; the corner-sharing octahedra are predominantly occupied by the former and the face-sharing octahedra by a 1:1 mixture of the two. On cooling through the temperature range 18 < T/K < 295 an increasing number of spins join an antiferromagnetic backbone running through the structure while the remainder show complex relaxation effects. At 3 K an antiferromagnetic phase and a spin glass coexist.